Chemical Precipitation and Coatings of Tin Selenide - Z Zainal; N Saravanan; K Anuar; M.Z Husein; W.M.M Yunus (Universitas Gadjah Mada, 2004)
Tin selenide were prepared chemically in alkaline aqueous solution. The crystalline powder was coated onto microscope glass slides using polyvinyl alcohol solution. The coatings were subjected to annealing at various temperatures to study the effect towards the structure, morphology and composition of the material. The product prepared was characterised using various techniques. The photoresponse for the samples were also studied. The photoelectrochemical (PEC) cell configuration was p-SnSe | (0.01 M K4Fe(CN)6¾0.01 M K3Fe(CN)6.3H2O¾0.1 M Na2SO4| Pt).